In silico analysis approach for screening new agents for breast cancer inhibitors based on 1,5-benzothiazepine - Neni Frimayanti; Marzieh Yaeghoobi; Hamid Namavar; Mashitoh Cindy Utari; Meiriza Djohari; Cindy Oktaviana Laia (Faculty of Pharmacy, Mahidol University, 2022)
Combination of similarity searching with docking and molecular dynamic simulations were performed. In this study, chalcone-based 1,5-benzothiazepine compound (i.e. MA9) was used as parent compound, since it exhibits potential enhancement and improvement of biological activity over doxorubicin (i.e. the common agent for cancer treatment). The main aim of this study was to explore a new potential inhibitor against breast cancer from a large database. To study this effect, several computational approaches were applied. Initially, seven compounds were observed according to the Euclidean distance and Tanimoto coefficient. Parent compound and all these seven compounds were docked into 1T46 protein active site. Docking results reported that ZINC4377306 and ZINC4377309 have exhibited binding free energy of -6.75 and -6.49 kcal/mol, respectively. In addition, they showed the binding interaction through hydrogen bond, van der Waals and other interactions with the notable residues around the active site. Both compounds were stable during the molecular dynamic simulation. Thus, ZINC4377306 and ZINC4377309 can be used as new potential agents against breast cancer as an early stage in drug discovery process.